Effects of Compatibilizer and Airflow Field on the Formation of Helical Microfibers via Melt Blowing. Issue 21 (17th October 2019) - Li, Hui; Huang, Hui; Zeng, Yongchun
ABSTRACT: We explore the approaches to improving the fabrication of melt‐blown helical microfibers, which have found the applications in sorption and filtration due to their unique morphology and excellent properties. To explore the effect of compatibilizer on the formation of helical microfiber, polypropylene (PP), polyurethane (TPU), and PP grafted with maleic anhydride (PP‐ g ‐MAH) are melt blown to fabricate microfibrous nonwovens. The results of rheological test and differential scanning calorimetry show that the addition of PP‐ g ‐MAH helps to increase the miscibility of the PP/TPU blends. Two die configurations are used to study the effect of airflow filed on the formation of helical microfibers. The computational fluid dynamics simulation results show that the modified swirl die intensifies the swirling strength of the melt blowing airflow. The addition of compatibilizer and modification of the airflow field both benefit the formation of helical microfibers from polymer blends. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2019, 57, 1423–1433 Abstract : Two approaches, addition of compatibilizer and modification of airflow field, have been shown to improve the fabrication of helical fibers via melt blowing. The compatibilizer PP‐ g ‐MAH increased the miscibility of polypropylene/polyurethane (PP/TPU) and the auxiliary device, under the die, modified the airflow field for intensifying the swirl air strength. These two factors result in a stronger interfacial interaction for the polymer components which benefit the fabrication of helical fibers via melt blowing.